If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-46=3(3x-1)-7
We move all terms to the left:
-46-(3(3x-1)-7)=0
We calculate terms in parentheses: -(3(3x-1)-7), so:We get rid of parentheses
3(3x-1)-7
We multiply parentheses
9x-3-7
We add all the numbers together, and all the variables
9x-10
Back to the equation:
-(9x-10)
-9x+10-46=0
We add all the numbers together, and all the variables
-9x-36=0
We move all terms containing x to the left, all other terms to the right
-9x=36
x=36/-9
x=-4
| 4x-47=4(3x-4)-7 | | 4(x-3)=3x-18 | | 4x-4*2=12-8 | | 2(y+7)=-2 | | 2(x+6)-4=6x+2 | | 5x-28/2-1=-10 | | 196=1/3*3.14*x^2*12 | | 1250=15x+500 | | 8v-14=3v+6 | | 10x6-26=5x6+4 | | 2x-4*3-4=2 | | 28+6x=6x-2 | | 2(3y-15)=5 | | 2d+6=46 | | 3x-9/3-2=10 | | 5x+10/2+3=13 | | 11m=(m.11)m | | 28+4x=9x-2 | | y÷-1=-12 | | 3x-4*3=12 | | 3x-4·3=12 | | 2x-8/2=10 | | 2x-8/2=19 | | x/x-1=1/x²-x | | -61x=61 | | -1/4(d)-2/5(d)=39 | | 3-(2x+6-(5x-8))= | | X=-y-7 | | 18y+11=-13+20y+6y | | -9f+9=2f-15-17f | | 8b-2=11b-20 | | 88=8(6−5v) |